Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 8 - Section 8.3 - Polynomial and Rational Functions - Exercise Set: 49

Answer

$P(a) = 2a-3$ $P(-x) = -(2x+3)$ $P(x+h) = 2x+2h-3$

Work Step by Step

If $P(x) = 2x-3$ $P(a) = 2a-3$ $P(-x) = 2(-x) -3 = -2x-3 = -(2x+3)$ $P(x+h) = 2(x+h)-3 = 2x+2h-3$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.